The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1515/kern-2021-0029
|View full text |Cite
|
Sign up to set email alerts
|

High rate X-ray radiation shielding ability of cement-based composites incorporating strontium sulfate (SrSO4) minerals

Abstract: Exposure of radioactivity applications should be handled reliably in repositories, radiotherapy rooms, and research centers built with cement-based composites which is generally used as an engineering barrier. The design of certain materials for radioactive exposure requires special handling considering the degradation mechanism of host composite environment and barrier capability. In this study, celestite (SrSO4) minerals having favoring properties for shielding ability was used as aggregates in barrier compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It was found that the obtained results were preferable to lead-based materials, The results of clay X-ray shielding were significantly high, reaching the best radiative attenuation rate of 99.79%, which is excellent compared to lead and tungsten [76,77]. These high shielding properties may be due to the components of the clay composed of various elements and metals with different contents, such as Al [78], Fe [79], Ti [80], Sr [81], and Si [82]. Consequently, the shielding rate values differed amongst the samples according to the proportions of the constituent elements.…”
Section: Effect Of Radiation Protection (Shielding)mentioning
confidence: 99%
“…It was found that the obtained results were preferable to lead-based materials, The results of clay X-ray shielding were significantly high, reaching the best radiative attenuation rate of 99.79%, which is excellent compared to lead and tungsten [76,77]. These high shielding properties may be due to the components of the clay composed of various elements and metals with different contents, such as Al [78], Fe [79], Ti [80], Sr [81], and Si [82]. Consequently, the shielding rate values differed amongst the samples according to the proportions of the constituent elements.…”
Section: Effect Of Radiation Protection (Shielding)mentioning
confidence: 99%